2007
DOI: 10.1093/nar/gkl1125
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of DNA methylation inside and outside of CTCF-binding regions in the transcriptional regulation of the telomerase hTERT gene

Abstract: Expression of hTERT is the major limiting factor for telomerase activity. We previously showed that methylation of the hTERT promoter is necessary for its transcription and that CTCF can repress hTERT transcription by binding to the first exon. In this study, we used electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) to show that CTCF does not bind the methylated first exon of hTERT. Treatment of telomerase-positive cells with 5-azadC led to a strong demethylation of hTERT 5′-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
218
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(235 citation statements)
references
References 38 publications
16
218
0
1
Order By: Relevance
“…In keeping, earlier studies showed that methylation of the hTERT promoter at the CTCF-binding site inhibited the binding of CTCF, thus derepressing hTERT in some human tumors. 16,17 Previous reports showed that a region between À578 and À300 bp upstream of the ATG initiation codon in the hTERT promoter, which corresponds to the domain identified in our study, 20,52 functions as a transcriptional silencer. This region includes MZF-2 and WT1 binding sites.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In keeping, earlier studies showed that methylation of the hTERT promoter at the CTCF-binding site inhibited the binding of CTCF, thus derepressing hTERT in some human tumors. 16,17 Previous reports showed that a region between À578 and À300 bp upstream of the ATG initiation codon in the hTERT promoter, which corresponds to the domain identified in our study, 20,52 functions as a transcriptional silencer. This region includes MZF-2 and WT1 binding sites.…”
Section: Discussionsupporting
confidence: 66%
“…16,17 Thus, it was not surprising to observe constitutive binding of CTCF to this proximal region in the cells used in this study, as this region is unmethylated in both NB4-LR1 and NB4-LR1 SFD variants. However, through this hTERT regulation by retinoids in maturation-resistant APL cells A Azouz et al binding, CTCF has been described as a repressor of hTERT.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Firstly, this cell line expresses MBD2 to a level similar to that observed in many cancer cell lines. 28,29 Secondly, the fact that epigenetic studies have been performed on this cell line by independent laboratories 8,30 has enabled us to exploit previously published data for validation purposes. Our aim here was to investigate the relationship between promoter occupancy by MBD2, the DNA methylation profile and gene expression.…”
Section: Preferential Binding Of the Methyl-cpg Binding Domain Proteimentioning
confidence: 99%
“…The TERT promoter has been shown to be the most important element of telomerase expression because it harbors binding sites for numerous cellular transcriptional activators and repressors that directly or indirectly regulate the gene expression (4). In addition, the high GC content around the transcription start site of the TERT promoter confers epigenetic regulation through methylation and chromatin remodeling (5,6).…”
mentioning
confidence: 99%